Consumer ethnocentrism: the relationship with domestic products evaluation and buying preferences - Muhammad @ Hashim, Nazlida; Che Razak, Razli (Universiti Utara Malaysia, 2004)
Malaysia is one ASEAN developing country, which has attracted the attention of foreign investors and marketers. ASEAN Free Trade Area(AFTA),which was realized in 2003, brings foreign products to Malaysian consumers with more affordable deals. The issue of globalisation that has been debated around the world could also carry the same impact or even more towards local products. One party that plays a major role in these issues is the Malaysian consumer. Do they think domestic products are of good quality? Are they willing to buy domestic products? These are the questions that should be answered in determining the future of domestic products. Consumer ethnocentrism is a marketing concept/construct that measures consumers' prejudice against imports. Consumers who score high on consumer ethnocentrism overestimate domestic products and underestimate imports. The objective of this study is to investigate whether consumer ethnocentrism has an impact on Malaysian consumers buying preferences and domestic products' evaluations. Findings from this study showed that more than 80% of the respondents were highly ethnocentric consumers. Results also showed that consumer ethnocentrism has a significant relationship to buying preferences and domestic products' evaluations. Despite positive evaluation on domestic products' evaluation, preferences to buy domestic products found to be varied across types of products. The sample most preferred to buy domestic food products and rated no preference to domestic cars and personal computers. The study also found that demographic variables of age, gender, income and education have no significant relationship with consumer ethnocentrism. The implications of the study and future research areas are also discussed.